Gender Differences Are a Leading Factor in 5-Year Survival of Patients with Idiopathic Pulmonary Fibrosis over Antifibrotic Therapy Reduction - Pasquale Tondo; Giulia Scioscia; Cosimo C. De Pace; Fabiola Murgolo; Federica Maci; Giulia M. Stella; Dalila Pescatore; Maria Pia Foschino Barbaro; Donato Lacedonia (Life)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease with a median survival of 3–5 years. Antifibrotic therapies like pirfenidone and nintedanib slow progression, but the outcomes vary. Gender may influence disease presentation, progression, and response to treatment. This study evaluates the impact of gender on the 5-year survival, pharmacological management, and clinical outcomes of patients with IPF. Methods: A retrospective cohort study of 254 IPF patients was conducted, with 164 (131 males:33 females) having complete data. Patients underwent spirometry, DLCO, and 6 min walk tests. Data on comorbidities, smoking, antifibrotic therapy type, dosage adjustments, and adverse events were collected. We used Kaplan–Meier survival curves and logistic regression to assess gender-related differences in outcomes. Results: Men had worse lung function at diagnosis (FVC 74.9 ± 18.5 vs. 87.2 ± 20.1% of pred.; p < 0.001) and a higher smoking prevalence (74% vs. 30%; p < 0.001). Women had better survival (51.2 vs. 40.8 ± 19.2 months; p = 0.005) despite more frequent biopsy use (36% vs. 17%; p = 0.013). Women tolerated longer therapy better (p = 0.001). No differences were found between patients receiving reduced antifibrotic dosing and those receiving full dosing. Conclusions: Gender has a significant impact on IPF outcomes, with women demonstrating better survival and tolerance to long-term therapy. In contrast, reducing antifibrotic treatment does not appear to significantly affect survival outcomes. These findings underscore the need for future research on gender-specific management approaches.